Research on the wear resistance of the material cylinder of an automatic injection molding machine during plastics processing - V.A. Honchar (Проблеми трибології)
The article presents experimental studies of the pressure in the material cylinder of the D3328 automatic injection molding machine when processing various plastics, as well as experimental studies of wear along the length of the material cylinder of the DB3328 automatic injection molding machine after processing PS 68-30 fiberglass. Specially designed strain gauge pressure sensors were used. Signals from the sensors were output to an oscilloscope through the amplifying equipment and recorded on an oscillogram. The magnitude and distribution of pressure along the length of the material cylinder will significantly affect the amount of wear of both the screw and the cylinder. It was established that the pressure in the material cylinder of automatic injection molding machines is distributed unevenly along its length. The nature of the pressure distribution along the length of the material cylinder when processing various materials: during the injection period, the maximum pressure occurs in the melt zone with a subsequent sharp decrease in the middle zone and a slight increase in the loading zone. At the same time, the nature of the pressure change for all materials is similar at a diametrical gap between the screw and the cylinder δ=0.17 mm. With an increase in the gap δ to 0.74 mm, the nature of the pressure distribution in the injection zone changes only when processing fiberglass, which is due to the partial ingress of glass fibers into the gap between the screw and the cylinder. Its magnitude and nature of the distribution along the length for different materials are different and depend on the physical, mechanical and rheological characteristics of these materials, the design of the screw and the technological modes of processing. The maximum pressure occurs in the melt zone during the period of material injection into the mold for 0.4-0.5 s.